Tales of the Bald Eagle Mountains in Central Pennsylvania - Shoemaker, Henry W. (Penn State University Press, 2026)
Tales of the Bald Eagle Mountains in Central Pennsylvania , originally published in 1912 by the Bright Printing Company, was the fourth of Henry Shoemaker’s many published volumes of fantastical tales about Pennsylvania’s folklore and wildlife. Focusing on what Shoemaker calls the “dark and sombre” Bald Eagle Mountains of Centre, Clinton, Lycoming, Juniata, and Union counties, the book provides a tale or legend centered on each mountain in the range. Stories of hunters and wolves, giant bears, quirky innkeepers and mysterious travelers, nefarious magic, brave Native American warriors, tragic murders, and anguished lovers are spun with the author’s usual flair for blurring the lines between myth and reality. Like Shoemaker’s other books, Tales of the Bald Eagle Mountains preserves a rich oral history, capturing what the author calls “a passing phase, a time and mode of life that will come no more,” and provides a window onto the cultural life and folklore of early central Pennsylvania.